MEDIA PEMBELAJARAN SEPAK BOLA BERBASIS APLIKASI “BOLA PINTAR” UNTUK SEKOLAH DASAR - Jeffry Trinando; Feri Yose Rizal; Muhammad Fathan Arisyi; Ade Fitri Ariska; Endang Sri Hevina; Herudi Lubis; Reza Hadinata (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop and evaluate the effectiveness of application-based soccer learning media for elementary school students. This learning media is designed to assist physical education teachers in delivering basic soccer technique materials in an interactive and interesting way. The research method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects of the study consisted of 60 students in grades 4-6 of elementary school and 6 physical education teachers in 3 elementary schools in City X. The results showed that the developed application received a "Very Good" rating from media experts (92%) and material experts (89%). The implementation of the application in learning showed an increase in students' understanding of basic soccer techniques by 45% and an increase in motor skills by 32% compared to conventional methods. In conclusion, application-based soccer learning media has proven effective in improving the understanding and skills of basic soccer techniques in elementary school students.